2020
DOI: 10.1002/anie.202001398
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Copper(I) Rotaxanes Mediate Sequential Click Ligations with All Reagents Premixed

Abstract: We have prepared NHC‐CuI complexes with a rotaxane structure and used them as sterically sensitive catalysts for one‐pot sequential copper‐catalyzed azide/alkyne cycloadditions in solutions containing all of the coupling partners premixed in unprotected form. Most notably, a photolabile and sterically encumbered complex first catalyzed the coupling of a less bulky azide/alkyne pair; after removing the protective macrocyclic component from the rotaxane structure, through irradiation with light, the exposed dumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
0
17
0
2
Order By: Relevance
“…Interlocked molecules, [1][2][3][4][5] such as rotaxanes and catenanes, contain cavities within which donor atoms can be positioned to bind metal ions. [6][7][8][9][10][11][12][13] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, 6,[14][15][16][17][18] were made by Sauvage and co-workers over 30 years ago. [19][20][21] More recently, 22 we demonstrated that rotaxanebased ligands can be used to produce complexes the non-interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted "entatic states" of metalloproteins, 23,24 suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interlocked molecules, [1][2][3][4][5] such as rotaxanes and catenanes, contain cavities within which donor atoms can be positioned to bind metal ions. [6][7][8][9][10][11][12][13] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, 6,[14][15][16][17][18] were made by Sauvage and co-workers over 30 years ago. [19][20][21] More recently, 22 we demonstrated that rotaxanebased ligands can be used to produce complexes the non-interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted "entatic states" of metalloproteins, 23,24 suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] More recently, 22 we demonstrated that rotaxanebased ligands can be used to produce complexes the non-interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted "entatic states" of metalloproteins, 23,24 suggesting that interlocked ligands could allow engineering of the properties of metal ions. However, to date, mechanically chelated metal ions with desirable catalytic behavior, 25,26 luminescent properties, 17,27 or unusual reactivity 16,18,21,[28][29][30] have only been reported based on coordination environments that can be accessed both with and without the mechanical bond. Thus, to our knowledge, the ability to engineer the fundamental properties of metal ions by controlling their coordination environment using the mechanical bond has not been demonstrated in prototypical functional systems, let alone the potential of the enforced environment of mechanically chelating ligands to allow the prediction of such properties.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocked molecules [1–5] contain cavities within which donor atoms can be positioned to bind metal ions [6–13] . Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, [6, 14–18] were made by Sauvage and co‐workers over 30 years ago [19–21] . More recently, [22] we demonstrated that rotaxane‐based ligands can be used to produce complexes the non‐interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted “entatic states” of metalloproteins, [23, 24] suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 97%
“…Interlocked molecules[ 1 , 2 , 3 , 4 , 5 ] contain cavities within which donor atoms can be positioned to bind metal ions. [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes,[ 6 , 14 , 15 , 16 , 17 , 18 ] were made by Sauvage and co‐workers over 30 years ago. [ 19 , 20 , 21 ] More recently, [22] we demonstrated that rotaxane‐based ligands can be used to produce complexes the non‐interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted “entatic states” of metalloproteins,[ 23 , 24 ] suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, [22] we demonstrated that rotaxane‐based ligands can be used to produce complexes the non‐interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted “entatic states” of metalloproteins, [23, 24] suggesting that interlocked ligands could allow engineering of the properties of metal ions. However, to date, mechanically chelated metal ions with desirable catalytic behaviour, [25, 26] luminescent properties, [17, 27] or unusual reactivity [14, 16, 18–21] have only been reported based on coordination environments that can be accessed with and without the mechanical bond. Thus, the ability to engineer the fundamental properties of metal ions by controlling their coordination environment using the mechanical bond has not been demonstrated in prototypical functional systems.…”
Section: Introductionmentioning
confidence: 99%